JDUHS: Successful Journey of Seven Years Since its Inception - Zahid Mirza (Journal of the Dow University of Health Sciences, 2014)
The history of medical writing is perhaps as old as that of the mankind itself with the earliest known medical publication, the Edwin Smith Surgical Papyrus dating back to 3000 BC written by the ancient Egyptians.1Publication of scientific periodicals and journals has been in vogue since the 17th Century and still continues to evolve with the ever-advancing scientific technologies. Medical journals provide a vibrant platform for the publication of research findings as well as sharing of useful professional experiences with the scientific community across the globe. We, in Pakistan, are now fortunately seeing an advancing movement of medical journalism with greater emphasis on peer-review, evidence base and high quality research.1-6